Pemanfaatan Minyak Jelantah Untuk Pembuatan Sabun Batang Bagi Anggota Karang Taruna Duri Pulo, Kecamatan Gambir, Jakarta Pusat - Pauhesti Pauhesti; Widia Yanti; Puri Wijayanti; Wildan Tri Koesmawardani; Gabey Jane (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
The amount of used cooking oil waste is thrown into the sewer, which over time will compress the sewer and can also pollute the environment. Therefore, it would be good if this used cooking oil is further processed into bar soap that can be used to wash clothes or other kitchenware. The process of making this bar soap uses a cold process, which does not use heating (stove). the chemical used is NaOH. The first stage is the purification of crude oil. Purification is done by soaking charcoal in used cooking oil, for about two days, then the used cooking oil is filtered. This purification does not remove the cloudy color of the used cooking oil, but the odor and turbid color of the used cooking oil is reduced. Then the purified used cooking oil is mixed into the lye, which is a mixture of water and NaOH. Then stir to mix until the solution is slightly thickened like the consistency of liquid soap. Then the mixture is put into a mold made of silicon, after 24 hours or after the soap is solid, the soap can be removed from the mold. This soap cannot be used yet, because it requires a curing process, which is a waiting time phase after solid soap, approximately 45 days. After going through the curing process, leaving it in the open air to ensure the water content evaporates well and the pH of the soap is normal. The solid soap produced from this training is able to clean the dirt on cooking utensils and can also be used as a clothes wash, and does not itch on the skin.